Church of the 21st-century - Szczerbowska, Katarzyna (2012)
The research of this dissertation is focused on history of church buildings and examples of modern churches as an introduction for the designing process of the 21st-century church building in southern Poland, Kraków. I would like to introduce the history of church buildings over the centuries and explain why understanding church history is so relevant while designing a modern church. Church history is a journey that brought us to where we are today. Christianity, unlike any other religion, is deeply rooted in history. In modern church buildings the expressive and symbolic value of architectural elements and forms have been rediscovered. This study is essential in order to understand what a church building is really about. What is more, try to answer the question, what a church building stands for nowadays. I introduce some examples of modern churches in order to present different approaches of the symbolism and the vision for the designs. Studying the form, functions, materials, symbolism; has determined my vision for approaching the project - the Church of the 21st-century, placed in one of the most incredible Polish cities - Kraków.